The Wiskott–Aldrich syndrome protein is required for positive selection during T-cell lineage differentiation - Pille, Melissa; Avila, John; Sanchez, Guillem Sanchez; Goetgeluk, Glenn; De Munter, Stijn; Jansen, Hanne; Billiet, Lore; Weening, Karin; Xue, Haipeng; Bonte, Sarah; Ingels, Joline; De Cock, Laurenz; et al. (Frontiers in Immunology, 2023)
The Wiskott-Aldrich syndrome (WAS) is an X-linked primary immune deficiency caused by a mutation in the WAS gene. This leads to altered or absent WAS protein (WASp) expression and function resulting in thrombocytopenia, eczema, recurrent infections and auto-immunity. In T cells, WASp is required for immune synapse formation. WAS patients show reduced numbers of peripheral blood T lymphocytes and an altered T-cell receptor repertoire. In vitro, their peripheral T cells show decreased proliferation and cytokine production upon aCD3/aCD28 stimulation. It is unclear whether these T-cell defects are acquired during peripheral activation or are, in part, generated during thymic development. Here, we assessed the role of WASp during T-cell differentiation using artificial thymic organoid (ATO)-cultures and in the thymus of humanized mice. While CRISPR/Cas9 WAS knocked-out hematopoietic stem and progenitor cells (HSPCs) rearranged the T-cell receptor and differentiated to TCR+ CD4+ CD8+ double positive (DP) cells similar to wildtype HSPCs, a partial defect in the generation of CD8 single positive (SP) cells was observed suggesting that WASp is involved in their positive selection. TCR repertoire analysis of the DP and CD8+ SP population, however, showed a polyclonal repertoire with no bias towards auto-reactivity. To our knowledge, this is the first study of the role of WASp in human T-cell differentiation and on TCR repertoire generation.